ACCOUNTABILITY FOR PROCUREMENT OF GOODS AND SERVICES AT THE REGIONAL SECRETARIAT OF NORTH MINAHASA REGENCY - Ade Irma Anthonie; Wilson Bogar; Jetty H. E. Mokat (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the form of public accountability and its implementation track record at each stage of the goods and services procurement process, as well as to identify structural, regulatory, and cultural factors that influence the creation of substantive accountability in the Regional Secretariat of North Minahasa Regency. The study uses a descriptive qualitative approach with data collection techniques of in-depth interviews, observation, and documentation of eleven key informants, including the Commitment Making Officer (PPK), procurement staff, the Regional Secretary, and representatives of the service user community. The results of the study indicate that public accountability has been formally institutionalized through hierarchical, legal, professional, and political mechanisms, but its implementation is still dominated by the logic of procedural compliance that focuses on completeness of documentation and accuracy of budget absorption. Tracing the accountability track record at four stages of procurement (planning, preparation and selection of providers, contract implementation, to handover of results) reveals consistent substantive gaps, where outcome evaluation and material accountability have not been highly institutionalized. Structural factors are characterized by fragmented coordination and the absence of a post-procurement evaluation unit; regulatory factors by the complexity of procedures without a results-based accountability clause; and cultural factors due to the orientation towards